DIGGING THE YOUTUBE VLOGGING IMPACT ON ENHANCING STUDENTS' SPEAKING PROFICIENCY - Soge, Edeltrudis Patrisia; Janggo, Wendelinus Oscar; Alinda, Marta (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2023)
In this study, the authors implemented Clasroom Action Research by using Youtube vlogging to improve students' speaking proficiency in two cycles. The primary objectives of this study were to describe the implementation of using this media and to find out how much students' speaking proficiency improved. Observations, interviews, field notes, documentation, and speaking tests were used in collecting the data. The authors evaluated the English test results of each student for data analysis. The samples of this study were twenty students of X-E-1 (tenth grade) of SMAK.ST. Gabriel Maumere. Quantitative data were collected from test scores, while qualitative data were collected from the progress of student activities, pleasant classroom atmosphere and interesting learning environment. The average score in the pre-test was 50.6%, with only 25% success rate in class percentages. During the first cycle, eight students (40%) reached the minimum standard of criteria, resulting in an average class score of 65.1%. In the second cycle, 17 students (85%) exceeded the standard, and the class average increased significantly to 77.4%. Consequently, it can be deduced that creating Youtube vlogs can augment students' spoken proficie